Adjusting Privatization : case studies from Developing countries - Adam, Christopher; Cavendish, William, 1964-; Mistry, Percy S.; Queen Elizabeth House (London : James Currey, 1992)
"An examination of privatization from an economic perspective. The authors evaluate the effects of ownership transfer on economic performance and market structure in seven developing countries: Jamaica, Trinidad and Tobago, Malaysia, Papua New Guinea, Sri Lanka, Kenya, and Malawi"--Handbook of Latin American Studies, v. 57.
Published in association with Queen Elizabeth House, University of Oxford.
"Based on evaluation of ... seven developing countries (Jamaica, Kenya, Malawi, Malaysia, Papua New Guinea, Sri Lanka and Trinidad and Tobago)"--Introd.
Includes bibliographical references (p. 377-390) and index.
Keywords: Privatization -- Developing countries -- Case studies; Privatization